Peran Perpustakaan Kota Sungai Penuh dalam Meningkatkan Literasi Masyarakat Desa - Haza Efrinandes; Fitri Handayani (Media Informasi, 2025)
The library is a place of literacy that offers various collections of books and information resources. This study aims to see the role of the Sungai Penuh City Library in improving the literacy of the village community of Sungai Penuh City. The method used is a case study with the selection of informants using purposive sampling techniques. The data analysis is used in three ways, namely: data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of the Sungai Penuh City Library in improving the literacy of the village community is: 1) Basic literacy: The Sungai Penuh City Library not only functions as a place to read and borrow books, but also as a center for developing basic literacy for children and an educational tourism destination for early childhood (PAUD / TK); 2) Reading Club: The Sungai Penuh City Library carries out training activities for village library managers to drive village reading corner activities; 3) Literacy training: The existence of the Social Inclusion-Based Library Transformation Program from the Sungai Penuh City Library is expected to provide village communities with opportunities to improve literacy and reading interest in the community; and 4) Collaboration with the community: The Sungai Penuh City Library Service previously collaborated with the Kincai Children's Volunteer Community to improve children's literacy in the Sungai Penuh City village.